Population Genetic Structure and Phylogeography of Camellia flavida (Theaceae) Based on Chloroplast and Nuclear DNA Sequences - Wei, Su-Juan; Lu, Yong-Bin; Ye, Quan-Qing; Tang, Shao-Qing (Frontiers in Plant Science, 2017)
Camellia flavida is an endangered species of yellow camellia growing in limestone mountains in southwest China. The current classification of C. flavida into two varieties, var. flavida and var. patens, is controversial. We conducted a genetic analysis of C. flavida to determine its taxonomic structure. A total of 188 individual plants from 20 populations across the entire distribution range in southwest China were analyzed using two DNA fragments: a chloroplast DNA fragment from the small single copy region and a single-copy nuclear gene called phenylalanine ammonia-lyase (PAL). Sequences from both chloroplast and nuclear DNA were highly diverse; with high levels of genetic differentiation and restricted gene flow. This result can be attributed to the high habitat heterogeneity in limestone karst, which isolates C. flavida populations from each other. Our nuclear DNA results demonstrate that there are three differentiated groups within C. flavida: var. flavida 1, var. flavida 2, and var. patens. These genetic groupings are consistent with the morphological characteristics of the plants. We suggest that the samples included in this study constitute three taxa and the var. flavida 2 group is the genuine C. flavida. The three groups should be recognized as three management units for conservation concerns.